2015
DOI: 10.14393/bj-v31n1a2015-30
|View full text |Cite
|
Sign up to set email alerts
|

Espécies potenciais para recuperação de áreas de floresta estacional semidecidual com exploração de minério de ferro na serra do espinhaço

Abstract: RESUMO:O objetivo deste trabalho foi avaliar a flora arbustiva-arbórea em um fragmento de floresta estacional semidecidual na região da Serra do Espinhaço para propor espécies para recuperação das áreas degradadas pela exploração de minério de ferro em ecossistemas congêneres. O levantamento florístico e estrutural da vegetação arbustivoarbórea foi realizado em setembro de 2007 por meio do método dos pontos quadrantes, tendo como critério de inclusão altura do fuste superior a 1,3 m. Os indivíduos foram estrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…Coinertia analysis showed that there is a significant association between the edaphic variables and the floristic composition of the 77 evaluated plots. The species with the high association with the infertile soils and rich in Fe and Al of the principal axis of coinertia was Xylopia sericea , a species of the late secondary ecological group (Meira‐Junior et al 2015). Individuals of this species are adapted to dry areas with low fertility, which may explain its strong association with the edaphic variables shown in the coinertia (Lorenzi 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Coinertia analysis showed that there is a significant association between the edaphic variables and the floristic composition of the 77 evaluated plots. The species with the high association with the infertile soils and rich in Fe and Al of the principal axis of coinertia was Xylopia sericea , a species of the late secondary ecological group (Meira‐Junior et al 2015). Individuals of this species are adapted to dry areas with low fertility, which may explain its strong association with the edaphic variables shown in the coinertia (Lorenzi 2000).…”
Section: Discussionmentioning
confidence: 99%
“…There are different methods used for the floristic survey, such as the free walking method, the quadrant method (AGUIAR, 2003;MEIRA JUNIOR et al, 2015;PEREIRA, 2015) or even the sample plot method, each with their advantages and disadvantages according to the evaluated or compared requirements. In this research, free walking methods and sample plots were considered.…”
Section: Introductionmentioning
confidence: 99%
“…Free walking consists of walking along pre-existing trails (ALVES et al, 2015;MEIRA JUNIOR et al, 2015;TONNELI, 2022) or simply at the researcher's pleasure in the area (GARCIA; ROMANGONOLO, 2015;FERRARESE et al, 2016;SCHLICKMANN et al, 2016;FRANCO, 2017;GARCIA et al, 2017;BARBOSA;SCABBIA, 2018;ZEIDAN;FERREIRA, 2020;MOURA et al, 2022;AGUIAR, 2015) with the intention of covering the largest and distinct possible sample, from which the vegetative and/or reproductive botanical material of the different specimens found along the path can be collected and/or identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…em florestas estacionais semideciduais ressalta o efeito de borda pelo menos até 30 m da borda, com variação ao longo da floresta de fatores bióticos como a umidade relativa, intensidade luminosa, temperatura e velocidade dos ventos.O levantamento florístico é um estudo, ou ainda uma ferramenta conforme Oliveira (1998), que proporciona reconhecer a riqueza de espécies da flora(SCHORN et al, 2014), ou seja, descrever qualitativamente a composição de espécies de determinado componente de modo rápido e eficaz na obtenção de informação(PINTO et al, 2013), inclusive em áreas recuperadas ou em estado de regeneração, para avaliar as condições atuais ou monitorar o desenvolvimento(MOURA et al, 2022). Com isto o levantamento florístico é o início para compreensão do ambiente, fornecendo informações que subsidiam estudos e atividades subsequentes, trabalhos de recuperação e conservação da biodiversidade, de restauração e conservação ambiental(OLIVEIRA, 1998) (ALVES et al, 2015;MEIRA JUNIOR et al, 2015;. TONNELI, 2022) ou simplesmente a gosto do pesquisador pela área (GARCIA;ROMANGONOLO, 2015;FERRARESE et al, 2016;SCHLICKMANN et al, 2016;FRANCO, 2017;GARCIA et al, 2017;BARBOSA;SCABBIA, 2018;ZEIDAN;FERREIRA, 2020; MOURA et al, 2022;AGUIAR, 2015) com a intenção de percorrer a maior e distinta área amostral possível, a partir do qual dá-se a coleta e/ O propósito deste estudo foi, além de levantar a riqueza florística das espécies arbóreas no fragmento florestal de área verde urbana e subsidiar estudos ambientais, acadêmicos e técnicos, posteriores, comparações e monitoramento, o de verificar a diferença entre a quantidade de espécies identificadas e o tempo de esforço em campo para realização do levantamento florístico entre o método de caminhamento livre e de parcelas fixas amostrais.…”
unclassified